Aplikasi Cendawan Pelarut Fosfat Indigenous Tanah Sawah Meningkatkan Ketersediaan dan Serapan P Padi Sawah - Hutagaol, Dermawan; Hasrizart, Iwan; Sofian, dan Ahmad (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2017)
Increasing P availaibility can be done using Phosphate solubilizing microorganism, but available information about indigenous phosphate solubilizing microorganism utilization from paddy soil that intensively fertilized with P is limited. The objectives of this experiment were to isolate, to select and to test the potential  of phosphate solubilizing fungi (PSF) in  increasing P availability, P uptake and rice production. Five isolates of PSF, referred to A1, A2, A3, A4 and A5 isolates, were belong to the Aspergillus genera. Field experiment was arranged in a randomized block design with one factor and 3 replications. The treatments consisted of 11 combinations of PSF and NPK fertilizer, i.e., without PSF + 100% rate of NPK fertilizer; PSF A1 + 50% rate of NPK fertilizer; PSF A1 + 100% rate of NPK fertilizer; PSF A2 + 50% rate of NPK fertilizer; PSF A2 + 100% rate of NPK fertilizer; PSF A3 + 50% rate of NPK fertilizer; PSF A3 + 100% rate of NPK fertilizer; PSF A4 + 50% rate of NPK fertilizer; PSF A4 + 100% rate of NPK fertilizer; PSF A5 + 50% rate of NPK fertilizer; PSF A5 + 100% rate of NPK fertilizer. Experiment results showed that application of  PSF isolates increased P availaibility, P uptake, rice growth and rice production significantly. Application of PSF A1 + 50% rate of NPK fertilizer was  the best treatment as indicated by the increased in weight of 1,000 rice grains, P availaibility and P uptake